Cours de composition par Louis Cherubini commencé le 3 février 1811 - Zimmermann, Pierre Joseph-Guillaume 1785-1853; Cherubini, Luigi 1760-1842 (s.l., 1811)
Course notes of lessons with Luigi Cherubini (1760-1842), commenced 3 February 1811. Apart from three pages, the manuscript is entirely in Zimmermann's autograph. The work is divided into seven books and more or less follows the published version of Cherubini's 'Cours de contrepoint et fugue' as printed later in 1835, albeit in an abridged version and with numerous differences to the text and musical examples. One of the most significant aspects of the manuscript is the date in Zimmermann's hand: "commencé le 3 février 1811". It is known that in the first two decades of the nineteenth century Cherubini compiled many didactic works at various intervals for the use of students. Until now his 'Cours de contrepoint et fugue' (in collaboration with Halévy) was thought to have been a much later work. The connections between Cherubini, Halévy and Zimmermann are close: Zimmermann became a pupil of Cherubini at the Paris Conservatoire around 1805, taught there himself from 1811 and was appointed professor of counterpoint and fugue in 1821, though he declined the position and taught piano only. In 1811 Halévy became a pupil of Cherubini's and may have well been taught by Zimmermann. The manuscript itself embodies some of Cherubini's earliest theoretical ideas, doubtless copied by Zimmermann from the author's original. On its publication, over twenty years later, the 'Cours de contrepoint et fugue' became one of the most popular and widely used didactic works in nineteenth-century Europe (notes by Lisa Cox, Antiquarian).
Digitized by iGuana, Spring 2022
Keywords: Conservatoire de Paris (France); 19th Century (1801-1900); Method; Composing; Paris (France); compositie; contrapunt; oud-nieuw; Palestrina; fuga; Marpurg; Martini, Padre